El bullying en niños y niñas de Educación Inicial. - Madril Quishpe, Karina Cecilia (2018)
The present research project was developed under the objective of deepening the study of Bullying in the children of Initial Education in the General School "Quisquis" of the Belisario Quevedo parish, Latacunga Canton, Cotopaxi Province in the school year 2016-2017, for the application of the project has been used a mixed qualitative and quantitative approach, descriptive, bibliographic-documentary and field, as research my techniques were conducted as interview with the question guides instrument addressed to teachers of the educational institution , Surveys for with parents and observation through the checklist made to the children of Initial Education, concluding that the main risk factors of aggressive behavior are expressed in behaviors and actions Who seek to harm another child. The consequences of bullying are mainly of a psychological type such as depression, anxiety, low self-esteem and low school performance that can be evidenced in changes in the child's behavior in the family and educational environment. As a result of the investigation it has been possible to establish that the parents perceive the existence of aggressions among the infants; at least 88% of the children have suffered some form of aggression. In the same sense, it is identified in the teacher with lacks strategies and guidelines to prevent, identify and manage bullying situations in the classroom, and finally it has been determined that the children have tried to integrate in a positive way despite their 49% of children at the initial level of education have difficulties to demonstrate their feelings positively, which reflects a poor level of emotional and social development, so it is necessary to work on the socio-affective development of infants . The contribution of the research has been to establish the negative effects of bullying in the initial education in order to establish institutional strategies to prevent it.